The influence of corporate and shari'ah governance mechanisms on the Islamic economic and financial performance of Islamic banks in Malaysia - Memiyanty binti Abdul Rahim (IIUM Institute of Islamic Banking and Finance, Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The responsibility and accountability of boards of directors and its effectiveness as part of governance mechanisms are important in assessing corporate performance. In the context of banking industry, corporate scandals and failures have attracted considerable amount of public attention. Hence, the need to understand the essentials of governance mechanisms have emerged. These mechanisms are crucial to ensure adequate accountability from the key players to protect not only the interests of shareholders but other stakeholders, in achieving performance. For Islamic banks, there is an emerging issue of inadequate, inappropriate and insufficient performance measurements. This study measures the acceptance of elements and ratios for the new performance measurement as well as develops a new performance measurement which is Islamic economic performance (IEP) as derived from Islamic economic objectives. This study also examines the influence of both corporate and Sharī'ah governance mechanisms on the Islamic economic and financial performance. In order to produce a reliable research, qualitative and quantitative research techniques have been used; via primary and secondary data collection methods, which covers interview (structured survey), questionnaire, annual reports and financial database. The sample of this study is 13 Islamic banks in Malaysia. The data had been gathered for three years since the start of the Shari'ah governance Framework (SGF) full implementation in 2012, until 2014. The data has been analysed via SmartPLS SEM to assess the influences of corporate and Sharī'ah governance mechanisms on Islamic bank performance. This study adopts the Islamic governance and accountability perspective which was developed by Abdul Rahman (1998) in deriving the theoretical framework and hypotheses. The IEP measurement has been accepted and developed in three elements such as need fulfilment and equitable distribution, economic growth and economic stability and seven ratios to represent the achievement of Islamic banks in Islamic economic objectives. The corporate governance mechanisms (CGM) and Sharī'ah governance mechanisms (SGM) were found to have a positive effect on the financial performance (FP) for Islamic banks in Malaysia. Not only that, SGM also has a positive effect on IEP. However, CGM brings no effect on IEP at all. The results indicated that the practices of corporate and Shari'ah governance mechanisms of Malaysian Islamic banks are considered to be sufficient as majority of the practices are aligned with most recommendations made by the relevant authorities. The findings of this study signify the importance of Islamic rules and regulations, moral values and ethics in enhancing Islamic economic and financial performance of the Islamic banks. This study also offers new measurement which can assist top management of Islamic banks to develop new strategies to further improve their banks' performances. It is hoped that this research can positively impact the policies and regulations in scrutinizing the roles, duties and responsibilities of board and Shari'ah committee in enhancing accountability, moral values and ethics matters. This study contributes to the body of knowledge as it develops and provides a set of new performance measures in measuring Islamic economic performance, which is also known as the M Score.